Effect of a nursing intervention to reduce risky alcohol consumption in older adults - Álvarez-Aguirre, Alicia (Universidad de Sonora, 2021)
Introduction: Alcohol consumption in older adults is a social and health problem, since it intensifies the harmful effect on them due to the biopsychosocial and spiritual changes as a result of the natural aging process. It affects the family members both emotionally and economically; there is more demand of health services in health institutions; it generates an increase in the consumption of financial and human resources. Objective: Evaluate the effect of an intervention to reduce risky alcohol consumption in older adults. Methodology: Quasi-experimental study carried out in a Gerontological Center in Mexico; the sample was comprised by 50 participants chosen through a non-probabilistic sampling. The intervention was based on the Rational Emotive Behavioral Therapy. AUDIT was applied, and a notebook with the personal data was available. Frequencies, percentages, measures of central tendency and dispersion were obtained, in addition to the Wilcoxon test. Results: Female individuals predominated (58%); 72% of the participants had incomplete elementary school studies; age ranged between 60 and 71 years (X̄= 64.42; SD = ± 2.80). When comparing the measurements of alcohol consumption, statistical significance was seen (Z = -6.160, p <.001) and the median was lower in the post-intervention measurement (Medianpre = 12 vs Medianpost = 7). Conclusions: The intervention showed an effect in reducing risky alcohol consumption.